First row transition metals on the ethanol Guerbet reaction: Products distribution and structural behavior of mixed metal oxides as catalysts - Metzker, Gustavo [UNESP]; Mora Vargas, Jorge Andres [UNESP]; de Lima, Livia Padilha [UNESP]; Perrone, Olavo Micali [UNESP]; Siqueira, Marcos Rechi [UNESP]; Varanda, Laudemir Carlos; Boscolo, Mauricio [UNESP] (Elsevier, 2021)
Described is the transformation of ethanol into 1-butanol, acetaldehyde and other products by the Guerbet reaction (GR) over mixed metal oxides (MMOs) as catalysts. The MMOs, in which Mg2+ was partially (20 mol%) substituted by Fe2+, Co2+, Ni2+, Cu2+, and Zn2+, were obtained from hydrotalcite precursors and the reactions conducted in a fixed bed flow reactor. EPR was used to observe oxygen vacancies after the catalytic reactions, which may be related to the ethanol reactivity due to the basicity enhancement of the catalyst. Carbon deposition, mostly filamentous, was observed in all catalysts and a trend between the metal-carbon bond energy and the percentage of deposited carbon was established. This correlation and the catalyst product distribution can be useful to tailor new catalysts. Using four parameters, ethanol conversion, 1-butanol and side-product selectivities and percentage of carbon deposition, Zn20MMO proved to be the best choice for GR.
Keywords: 1-Butanol; Ethanol; First-row transition metals; Guerbet reaction